Assessment of Coagulation Parameters in Women Affected by Endometriosis: Validation Study and Systematic Review of the Literature - Ottolina, Jessica; Bartiromo, Ludovica; Dolci, Carolina; Salmeri, Noemi; Schimberni, Matteo; Villanacci, Roberta; Viganò, Paola; Candiani, Massimo (Diagnostics (Basel), 2020)
The presence of endometriosis determines an inflammatory response locally. The objective of this validation study and systematic review was to assess systemic levels of coagulation and inflammatory parameters in women with or without the disease. We conducted a retrospective analysis of a database prospectively collected from January 2017 to February 2020 including n = 572 women who underwent laparoscopic surgery for endometriosis (cases, n = 324) or other benign gynecologic diseases (controls, n = 248). Inflammatory markers and coagulation parameters were determined. An advanced systematic search of the literature on the same parameters was conducted up to April 2020. A significantly higher neutrophil count was found in endometriosis patients. Patients with endometriomas and stage III–IV disease had a significantly lower absolute lymphocyte count and shortened activated partial thromboplastin time (aPTT) values. In the final regression model, aPTT retained significant predictive value for stage III–IV endometriosis (odds ratio (OR) = 0.002, 95% confidence interval (CI) = 0.00–0.445; p = 0.024). Results from the n = 14 included studies in the systematic review are characterized by a high variability, but some consistency has been found for alterations in thrombin time, platelet-to-lymphocyte ratio, and neutrophil count associated with endometriosis. Modest systemic changes of some inflammatory and coagulation parameters are associated with endometriosis. Indeed, all the modifications detected are still within the normal reference intervals, explaining the high heterogeneity among studies.